Penerapan Model Pembelajaran Berbasis Masalah pada Mata Pelajaran PPKN sebagai Upaya Membentuk Sikap Demokratis Siswa SMA di Kota Lhokseumawe - Munawarah Munawarah; Ruslan Ruslan; Maimun Maimun (Departement of Mathematics Education, 2023)
The learning process requires a model that can help deliver learning, one of which is the problem based learning model. Problem-based learning is an innovative learning model that can provide active learning conditions for students. This research aims to determine the application of the problem-based learning model in Civics subjects as an effort to form democratic attitudes for high school students in the city of Lhokseumawe. To determine efforts to foster democratic attitudes in students through a problem-based learning approach. To describe the obstacles in forming democratic attitudes for high school students through a problem-based learning approach. The method used is a qualitative research method. Data collection techniques use interview and documentation methods. The informants in this research were 9 PPKn teachers in the city of Lhokseumawe. The results of the research show that problem-based learning influences the formation of students' democratic attitudes. Problem-based learning focuses more on developing understanding of democratic concepts, as well as strengthening democratic values. The democratic attitude of students that emerges in the problem based learning model is an open attitude towards other people's opinions, producing decisions and freedom of opinion. The two factors created are (1) internal factors that hinder teachers in the learning process, which lies in the teacher's low understanding of problem-based learning (2) The external factor that hinders teachers in the learning process lies in the lack of learning books.